Pedagogical and Psychological Opportunities for Forming Skills in Future Teachers (Diversity Research: Journal of Analysis and Trends, 2023)
In this article, the psychological essence of tolerance and the importance of the formation of tolerance in future pedagogues today, the institutional model of the formation of tolerance are highlighted